Investigation of energy dissipation performance of triangular stepped spillways - Yalcin, Eyyup Ensar; Ikinciogullari, Erdinc; Kaya, Nihat (Pamukkale Univ, 2024)
Stepped spillway can dissipate most of the flow energy in the discharge channel with the steps along the discharge channel. These spillways, which have been widely used for centuries due to the contribution of the steps in energy dissipation, have been the subject of many academic studies. In this study, the energy dissipation performance of triangular stepped spillways are investigated using Flow-3D software. A total of nine analyzes were carried out using three different models and three different discharges. As a result of the analyzes carried out, it was concluded that the energy dissipation ratio increases with the increase of the step depth (h(t)), the triangular stepped spillways can dissipate up to 78% more energy than the conventional stepped spillways, and this rate decreases as the transition flow regime is passed.
Keywords: Triangular stepped spillway; Energy dissipation; Flow3D; Computational fluid dynamics (CFD)